Illinois Tool Works Inc. a corporate strategy paper - Marrero, Susan C.
This corporate strategy paper on Illinois Tool Works Inc. (ITW) by Susan C. Marrero explores the strategic frameworks and management practices that have enabled ITW to become a leading multinational manufacturer. The paper emphasizes how ITW uses strategic planning to maintain agility and profitability across its varied business segments. Through case analysis, it investigates ITW’s competitive strengths, challenges in global integration, and opportunities for innovation and market expansion. Key strategic recommendations include leveraging core capabilities, reinforcing supply chain efficiencies, and expanding into high-growth regions.